Agricultural Land Values Increase as Citrus Land Values Decrease: 2002 Survey Results - John E. Reynolds (EDIS)
This is EDIS document FE360, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published October 2002.